A facile and efficient four-step enantioselective synthesis of (+)-vernolepin from (+)-minimolide, the major germacranolide of Mikania minima - Bach, Sandra M. (2011)
Enantiomerically pure (+)-vemolepin was semi-synthesized for the first time using the synthon (6S,7R,8S)-8,14-diacetoxy-15-hydroxygermacra-1(10),4,11(13)-trien-6, 12-olide [(+)-minimolide], the major sesquiterpene lactone of the Argentinean vine Mikania minima. After performing four consecutive reactions (Cope rearrangement, two oxidations, and selective hydrolysis of the acetate groups) on the synthon (+)-minimolide, a (+)-vernolepin yield of ca. 40% was achieved, proving to be a suitable semi-synthetic strategy for the production of quantities between 0.5-1.0 g of (+)-vernolepin. The transformations described here mimetize the biogenetic pathway for the production of (+)-vernolepin in the genus Vernonia. The synthesized (+)-vernolepin, but not its precursors, shows antifungal activity similar to amphotericin B. The semi-synthesis reported here combines affordable and easily available chemical reagents with classical organic methodologies.